A Review of the Impacts of Climate Change on Tourism in the Arid Areas: A Case Study of Xinjiang Uygur Autonomous Region in China - Wang Shijin; Ma Xinggang; Xie Jia (Advances in Meteorology)
Tourism is more sensitive and susceptible in global arid regions to climate change than other sectors, and climate change mainly affects the behavior of tourists, selection of tourist destinations, tourism resources, and tourism safety. China’s Xinjiang Uygur Autonomous Region (XUAR) is a representative area of the global arid region. To review its comprehensive impacts of climate change on tourism has indicative significance for the global arid region tourism industry to cope with climate change impacts. On the whole, the impacts of climate change on tourism in the XUAR will coexist with opportunities and challenges both at present and in the future. The XUAR is experiencing or will experience climatic process of warming and wetting. For the tourism climate comfort and extension of suitable travel period, the opportunities far outweigh the risks (high reliability). However, future climate change is expected to have great negative effects on cultural heritages, glacier and snow resources, and agricultural landscapes in arid areas of northwest China (high reliability). The above impacts are potential and long-term, and the measures should be taken as soon as possible to mitigate and adapt to climate change challenges to tourism.